Oral anticoagulants: a frequent challenge for the emergency management of acute ischemic stroke - Rizos, Timolaos; Horstmann, Solveig; Jenetzky, Ekkehart; Spindler, Marcia; Gumbinger, Christoph; Möhlenbruch, Markus Alfred; Ringleb, Peter A.; Hacke, Werner; Veltkamp, Roland (Cerebrovascular diseases, 2012)
Background: The emergency management of patients with acute ischemic stroke (IS) using oral anticoagulants (OAC) represents a great challenge. Effective anticoagulation predisposes to bleeding and represents a contraindication for systemic thrombolysis. However, patients on OAC can receive intravenous thrombolysis with recombinant tissue-type plasminogen activator if the international normalized ratio (INR) does not exceed 1.7, but data regarding the risk of hemorrhagic complications are highly controversial. Neurointerventional recanalization of intracranial artery occlusion represents an alternative option in OAC patients with acute IS. The proportion of OAC users among consecutive patients who suffer from acute IS or transient ichemic attacks (TIA) is unknown. Methods: A prospective observational study, consecutively enrolling all patients with IS or TIA admitted to our neurological emergency room (ER), was performed between August 2009 and February 2011. Basic demographic variables, present use of OAC, severity of stroke, cardiovascular risk factors, INR values and the symptom onset to presentation time were recorded. In IS patients on OAC presenting within 4.5 h after symptom onset, management was analyzed. In thrombolysed IS patients, bleeding events were documented. Outcome was assessed after 3 months. Results: During the study period, 12,237 patients were admitted to our neurological ER. IS or TIA were diagnosed in 2,074 (16.9%). Complete data were available for 1,914 of these subjects (92.3%); 53.8% were male (median age: 72 years). 69.7% suffered IS, 30.3% TIA. OAC were being used by 8.7% of all patients. OAC patients were older than non-OAC patients (78 vs. 72 years, p < 0.001). Subtherapeutic INR values (<2.0) were found in 67.3% of OAC patients with IS. 54.8% of all OAC IS patients presented at the ER within ≤4.5 h after the event (57/104). An INR ≤1.7 - compatible with systemic thrombolysis - was present in 33/57 patients (57.9%). Recanalization therapy was performed in 21/57 patients (36.8%). No difference in symptomatic or fatal intracerebral bleedings between thrombolysed patients with and without prior OAC use was observed (p = 0.720 and 0.135, respectively). Multivariable analysis of predictors of the 3-month outcome in IS patients revealed that prior medication with OAC was neither associated with an unfavorable clinical outcome after 3 months in the whole population of stroke patients (p = 0.235) nor in patients in whom recanalization approaches were used (n = 306; p = 0.271). Conclusions: Oral anticoagulation represents a frequent challenge for the emergency manangement of IS. A considerable proportion of anticoagulated IS patients appears to be eligible for thrombolysis. Establishing standardized treatment procedures in these patients is warranted.
Gesehen am 05.07.2018